Behaviours of healthcare professionals towards difficult patients: A structural equation modelling study - Cerit, Kamuran; Karataş, Tuğba; Ekici, Dilek (Nursing ethics, 2020)
Background: Some patients are stigmatised as difficult patients by healthcare professionals. This phenomenon has great many negative consequences. The behaviours of healthcare professionals towards difficult patients are important. Objective: To explore the behaviours of all healthcare professionals towards difficult patients. Research Design: This study was based on a cross-sectional research design using structural equation modelling. Participants and Research Context: Two hundred and fifty-four healthcare professionals were involved in the study in Turkey. ‘Participant Information Form’ and the ‘Healthcare Professionals Behaviour Assessment Questionnaire For Difficult Patient’ were used to collect data from participants. Ethical Consideration: Ethical approval was obtained from Gazi University Ethics Committee for the study. Informed consent of the participants in the study was taken and the confidentiality of the participants was ensured. Findings: It was explored that the behaviours of healthcare professionals towards difficult patients were categorised into ethical, supportive and negative. The highest mean score was supportive behaviour and the least mean score was negative. According to structural equation modelling, the most important predictor of difficult encounters was an ethical dimension. One-unit increase in ethical behaviour contributed to 0.92 unit increase in positive patient behaviour. Discussion: Patients generally are perceived as ‘difficult patient’ by the healthcare professionals, so the patients’ treatment and care services are affected negatively due to healthcare professionals’ negative beliefs and attitudes. The healthcare professionals should behave supportively towards difficult patients. Conclusion: Healthcare professionals should be aware of management strategies in dealing with difficult encounters. The behaviours of healthcare professionals should be improved in a positive way and awareness of ethical dimension of difficult encounters should be increased.